Forging alternatively sacred spaces in Singapore's integrated religious marketplace - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2020)
This paper expands the notion of sacred space within the geographies of religion by arguing that spaces of religious praxis need to be understood in relation to the broader spatial logics within which they are embedded. Given that the spatial logics of urban environments tend to be secular and neoliberal in nature, it considers how religious groups respond to the realities of the marketplaces in which they operate by forging “alternatively sacred” spaces. These spaces augment the appeal of religious groups in non-religious ways, thus making them more competitive players in a religious marketplace. Specifically, it explores how independent churches in Singapore create alternatively sacred spaces that are used for religious purposes, although their appeal and affective value do not accord with more traditional understandings of how sacred spaces should look, feel, or otherwise be engaged with. These spaces are designed to appeal to younger people, and to draw non-Christians to Christian spaces, and Christians to alternatively religious spaces. The extent to which they appeal to these groups provides insight into reimagination of religion under market conditions, spatial politics of value, and ideological fissures between different Christian communities.